Suicides in Penitentiaries and Detention Centres - Rzeźniczak, Angelika (Teisė, 2020)
This article deals with the problem of suicides and self-inflicted injuries in prisons and detention centres. The main aim of the article is an attempt to determine the characteristics of a prisoner who performs self-destructive behavior. The second aim is to get to know better the problems of inmates committing suicides. Knowing these problems will help to find preventive solutions. The article describes the information collected during interviews with 18 people, including: prisoners (women and men), prison chaplains, directors of prisons, officers and employees of penitentiary units.
Keywords: suicides; self-inflicted injuries; the penitentiary system; prison; pre-trial detention